On the Asymptotic Boundary Condition at the Free-Fluid/Porous-Medium Interface in Periciliary Layer due to the Ciliary Movement - Sudaporn Poopra; Kanognudge Wuttanachamsri (Mathematical Problems in Engineering, 2022)
The purpose of this study is to study the movement of the periciliary (PCL) fluid due to the ciliary locomotion. In this research, because the bundle of cilia is considered instead of a single cilium, Stokes–Brinkman equations in a macroscopic scale are employed to find the velocity of the PCL fluid. When the cilia are perpendicular to the horizontal plane, the PCL consists of only the cilia. The inclination of cilia (cilia make an angle θ θ < 90 ∘ to the horizontal plane) results in two different domains in the PCL, the regions comprising and not comprising cilia. The main objective of this study is to determine the appropriate boundary conditions of the velocity between these two regions where the PCL fluid is moved by self-propelled cilia rather than the pressure gradient. A matched asymptotic expansion method is applied to the Stokes–Brinkman equations to determine the constraints. Two boundary conditions at the interface are obtained and the velocity of the PCL fluid at the top of PCL can be used to be the boundary conditions at the bottom of the mucus layer to determine the velocity of mucus. This model can help engineers to build devices to treat patients who have problem with the respiratory system. Applications include modeling fluid flow through filters such as engine filter and rice fields.
Keywords: Lattice Boltzmann Simulation Studies; Heat and Mass Transfer in Porous Media; Aerosol Filtration and Electrostatic Precipitation